A cis-acting element from the Epstein-Barr viral genome that permits stable replication of recombinant plasmids in latently infected cells. - Yates, J (1984)
The Epstein-Barr viral (EBV) genome of approximately equal to 170 kilobase pairs (kbp) is maintained as a plasmid in human B lymphoblasts transformed by the virus. We have identified a cis-acting element within 1.8 kbp of the viral genome that allows recombinant plasmids carrying it to be selected at high frequency and maintained as plasmids in cells latently infected by EBV. This functional element(s) requires a segment of DNA at least 800 bp and at most 1800 bp long, which contains a family of 30-bp tandem repeats at one end. Since this region confers efficient stable replication only to plasmids transfected into cells containing EBV genomes, its function probably requires trans-acting products encoded elsewhere in the viral genome.